Poetry Among the Arabs Until the End of the Umayyad Caliphate Period (Raparin Journal of Humanities (RJH), 2025)
This study discusses the emergence of poetry among the Arabs, in which their interest in poetry as a literary source is presented, according to the historical periods, with the fundamental changes that have occurred to poetry in terms of subject matter and the theme of texts in each period or era. Meanwhile, the role of poetry and poets and their influences on society and individuals are also discussed. In addition, it has been mentioned that the poets were attached to their tribes and clans, or that they were close and affiliated with the authorities, whether this was due to praise of the authority or condemnation of their opponents. All these are reflected in the texts and thus several poetic texts and proof have been cited to confirm them, as the nature of the research seems to require this approach. Despite the importance of poetry and the poetic language as well as paying much attention to it in those eras, poetry also played a role in narrating events, even though history had not recorded many events before. Here it is noticed that poetry played the role of narrating and recording the events and anecdotes of the past, and from this point of view, it can be said that whoever wants to become familiar with the situation of Arab society and some of their social, cultural and even political customs either in pre-Islamic period or at the beginning of Islamic era, at least it is necessary to go back to some of the poems of those poets who lived near those eras. Although poets have often mixed events with their imagination and fantasy, so it may not be possible to get a completely real picture of those periods, whatever considered historical reason can be drawn from it, and then by highlighting these literary texts, some hidden and dark sides of those eras can be revealed.